2015
DOI: 10.1038/nature16153
|View full text |Cite
|
Sign up to set email alerts
|

Thermal vesiculation during volcanic eruptions

Abstract: Terrestrial volcanic eruptions are the consequence of magmas ascending to the surface of the Earth. This ascent is driven by buoyancy forces, which are enhanced by bubble nucleation and growth (vesiculation) that reduce the density of magma. The development of vesicularity also greatly reduces the 'strength' of magma, a material parameter controlling fragmentation and thus the explosive potential of the liquid rock. The development of vesicularity in magmas has until now been viewed (both thermodynamically and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 33 publications
6
60
0
Order By: Relevance
“…We assessed the relative volume fractions of gas and ash erupted during a single explosion and demonstrated that plumes from small‐to‐moderate size events at Santiaguito are extremely gas rich. The minor volume fraction of ash in the plume suggests that these events may not involve significant fragmentation of magma in the conduit and concurs with the recent suggestion that local sacrificial fragmentation along fault zones, due to shear‐induced thermal vesiculation, may be at the origin of such events [ Lavallée et al , ].…”
Section: Discussion and Conclusive Remarkssupporting
confidence: 84%
See 1 more Smart Citation
“…We assessed the relative volume fractions of gas and ash erupted during a single explosion and demonstrated that plumes from small‐to‐moderate size events at Santiaguito are extremely gas rich. The minor volume fraction of ash in the plume suggests that these events may not involve significant fragmentation of magma in the conduit and concurs with the recent suggestion that local sacrificial fragmentation along fault zones, due to shear‐induced thermal vesiculation, may be at the origin of such events [ Lavallée et al , ].…”
Section: Discussion and Conclusive Remarkssupporting
confidence: 84%
“…Explosions throughout the past decade have been of small to moderate size and have produced volatile‐rich plumes with relatively minor proportions of ash [ Yamamoto et al , ]. Recent petrological and geophysical analyses suggest that these small gas‐and‐ash explosions are not triggered by typical magmatic fragmentation but rather through sacrificial fragmentation that occurs along fault zones due to shear‐induced thermal vesiculation [ Lavallée et al , ].…”
Section: Activity At Santiaguitomentioning
confidence: 99%
“…The processes triggering “vulcanian” gas‐and‐ash explosions at active lava domes remain widely debated as competing hypotheses exist at both all‐encompassing (Chouet et al, ) and volcano‐specific (Hall et al, ) scales. Vulcanian events have been attributed to a range of processes, from the ascent of a fresh batch of bubbly magma in the shallow conduit (Cassidy et al, ) and gas pressure accumulation due to fracture sealing (Kendrick et al, ; Okumura & Sasaki, ) healing (Gardner et al, ; Lamur et al, ) and cyclic gas fluxing (Michaut et al, ) to the development of shear fractures along the margins of volcanic conduits during ascent of highly viscous magma (Lavallée et al, ; Lensky et al, ; Tuffen et al, ). On the other hand, there is a general agreement on the processes that result in fracturing of parts of the dome during explosive activity to allow the ejection of ash‐laden plumes.…”
Section: Introductionmentioning
confidence: 99%
“…In a conduit, this can relate to magma decompression driven by ascent, plug slip or edifice failure, as well as an increase in magma temperature (e.g., Sparks, 1978;Alibidirov and Dingwell, 1996;Lensky et al, 2008;Lavallée et al, 2015). The coincidence between dense borders of vesicular clasts and H 2 O depletion reflects an H 2 O concentrationdependent nucleation response to a decompression event ( Figure 5B; Castro et al, 2012).…”
Section: Vesicular Clast Textural Characteristics-vsdmentioning
confidence: 99%